Transcultural skills for early childhood professionals - Radjack, Rahmeth; Bossuroy, Muriel; Camara, Hawa; Touhami, Fatima; Ogrizek, Anaïs; Rodriguez, Juliette; Robin, Marion; Moro, Marie Rose (Frontiers in Psychiatry, 2023)
Context Transcultural skills are especially useful for those involved in the perinatal period, when parents and babies must adapt to one another in a setting of migration a long a focus of transcultural clinical practice. Objective The aim of this article is to provide useful transcultural skills for any health care worker (e.g., psychologists, child psychiatrists, midwives, family doctors, pediatricians, specialized child-care attendants, and social workers) who provide care or support to families during the perinatal period. It highlights the cultural aspects requiring attention in relation to representations of pregnancy, children’s needs, obstetric complications, and postnatal problems. Taking into account the impact of culture on clinical evaluation and treatment can enable professionals to distinguish what involves cultural representations of pregnancy, babies, and sometimes of disease from what is associated with interaction disorders or maternal psychopathology. Methods After explaining the relevance of transcultural clinical practices to provide migrant mothers with better support, we describe 9 themes useful to explore from a transcultural perspective. This choice is based on the transcultural clinical practice in our specialized department. Results The description of these 9 themes is intended to aid in their pragmatic application and is illustrated with short clinical vignettes for specific concepts. We describe situations that are extreme but often encountered in liaison transcultural clinical practice for maternity wards: perinatal mourning with cultural coding, mediation in refusal of care, cultural misunderstandings, situations of complex trauma and of multiple contextual vulnerabilities, and difficulties associated with acculturation. Discussion The transcultural levers described here make it possible to limit cultural misunderstandings and to promote the therapeutic alliance. It presupposes the professionals will concomitantly analyze their cultural countertransference and acquire both the knowledge and know-how needed to understand the elements of cultural, political, and social issues needed to develop clinical finesse. Conclusion This combined theoretical-clinical article is intended to be pedagogical. It provides guidelines for conducting transcultural child psychiatry/psychological interviews in the perinatal period aimed at both assessment and therapy.